2017
DOI: 10.11114/jets.v5i9.2576
|View full text |Cite
|
Sign up to set email alerts
|

A Needs Assessment for the Adoption of Next Generation Science Standards (NGSS) in K-12 Education in the United States

Abstract: Since its inception, the Next Generation Science Standards (NGSS) blue print has attracted interest from more than 40 states in the United States. The overall objective of these proposed changes is to align K-12 science education with current trends in technology and career needs. However, the assessment of teacher preparedness and classroom technology needs is still a critical factor in the implementation of these changes. Our study conducted a needs and preparedness assessment using online surveys on public … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
5
4

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 15 publications
4
5
4
Order By: Relevance
“…This result is in keeping with the findings of [ 2 , 3 , 18 ] in which practicing and developing models ranked "low." However, this result differs from the findings of [ 14 , 27 30 ] which revealed a “good” level of the NGSS practices in teachers’ performance.…”
Section: Study Resultscontrasting
confidence: 99%
See 2 more Smart Citations
“…This result is in keeping with the findings of [ 2 , 3 , 18 ] in which practicing and developing models ranked "low." However, this result differs from the findings of [ 14 , 27 30 ] which revealed a “good” level of the NGSS practices in teachers’ performance.…”
Section: Study Resultscontrasting
confidence: 99%
“…Table 4 shows that the general mean of this practice ranked "medium" at (3.03). This result mirror the findings of [ 2 , 3 , 14 , 28 – 30 ] which revealed a “good” or “medium” level of the NGSS practices in teachers’ performance.…”
Section: Study Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…In general, the results of the current study were in line with the results of the previous studies that showed the need for the development and improvement of the science courses according to the Next Generation Science Standards [8] [10]- [15] [33]. The current study differs from these studies in a very important aspect in which it worked to evaluate the science books in a whole stage and in all dimensions and fields of the Next Generation Science Standards.…”
Section: Fields Of Analysissupporting
confidence: 87%
“…But these resources are often lacking. In the context of the NGSS, there is, for instance, increasing concern about, on the one hand, the readiness of teachers, students, and staff and, on the other, the availability of needed classroom technology resources to support the implementation of these new standards (Harris et al, 2017). Supportive teaching materials are essential because the underlying philosophy of the behavior of complex systems does not become a part of a student's thinking when experienced only through reading and listening (Meadows, 2007).…”
Section: Introductionmentioning
confidence: 99%